Pemanfaatan Zat Besi Dalam Makanan Laut (Ikan Laut) Pada Ibu Hamil Untuk Mencegah Stunting Di KelurahanPulau Simardan Tanjung Balai Tahun 2022 - Eliza Bestari sinaga; Meni Fuzi Astuti Tanjung (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
Based on the results of the latest basic health research from the Ministry of Health, at least 30.8 percent of children under five in Indonesia have a height that is not in accordance with their age or commonly known as stunting. Chronic malnutrition does not only have an impact on physical failure to grow or low birth weight, small, short, and thin. However, it is also susceptible to non-communicable diseases and can inhibit brain growth which can interfere with motor growth. The nutritional content of fish is very, very relevant to support stunting prevention programs, especially in the first 1,000 days of life. superiority of fish to prevent stunting or stunting due to chronic malnutrition that still stalks Indonesian children. These advantages include containing high Omega 3 fatty acids for the development of the eyes, brain, and nervous tissue as well as having a complete amino acid composition. So that it is easily digested and absorbed by the body, as well as a source of vitamin D and calcium for bone growth